Trait variation and trait stability in common marmosets (Callithrix jacchus) inhabiting ecologically distinct habitats in northeastern Brazil. Issue 7 (13th June 2019) - Garber, Paul A.; Caselli, Christini B.; McKenney, Anna C.; Abreu, Filipa; De la Fuente, Maria Fernanda; Araújo, Arrilton; de Fatima Arruda, Maria; Souto, Antonio; Schiel, Nicola; Bicca‐Marques, Júlio César
Abstract: Understanding the set of factors that promote and constrain a species' ability to exploit ecologically distinct habitats is central for addressing questions of intraspecific variability in behavior and morphology. In this study, we compared newly collected data with published data on body measurements, group size and composition, daily path length, home range, and reproductive output in wild common marmosets naturally inhabiting two contrasting environments in northeastern Brazil: the Atlantic Forest (AF), which is characterized by high biodiversity and reduced seasonality in food availability and the Caatinga (CAT), which is characterized by a severe hot and dry season lasting from 5 to 11 months, drought‐resistant plant species, and reduced primary productivity. Despite marked differences in ecological conditions, CAT marmosets and AF marmosets differed minimally in daily path length, home range, reproductive output, and infant survivorship. CAT marmosets were found to live in smaller groups containing fewer adult females than AF marmosets, and also were characterized by a greater surface area to body mass ratio, a trait that may represent an adaptation to the hot and dry conditions of the Caatinga. We propose that in conjunction with body mass reduction, minor adjustments in behavior, the exploitation of cacti as a source of water and nutrients, and access to exudates as a dependable year‐round food resource, common marmosets successfully used the same adaptive pattern to maintain high reproductive output and infant survivorship in exploiting these two ecologically distinct environments. Abstract : Despite naturally inhabiting two ecologically distinct habitat in northeastern Brazil, the Caatinga (hot and dry thorn scrub forest, averaging 620 mm rainfall per year) and the Atlantic forest (rainforest characterized by high animal and plant biodiversity and receives up to 2, 000 mm of rainfall per year), common marmosets inhabiting these sites did not differ in daily path length, home range area, activity budget, reproductive output, or offspring survivorship. We argue that common marmosets exploited both habitats in very similar ways using an adaptive pattern characterized by extensive exudate feeding, cooperative infant caregiving provided principally by adult males, and high reproductive output by a sovereign breeding female. Adult Caatinga marmosets were distinct from Atlantic Forest marmosets in reduced body mass (weighing 15% less), the consumption of water‐rich cacti fruit, flowers, and flesh, and an increase in their ratio of surface area to body mass. We hypothesize that these differences function to provide increased efficiency in water conservation and rates of non‐evaporative heat loss in the hot and dry Caatinga environment. Research Highlights: Despite naturally inhabiting two ecologically distinct habitats in northeastern Brazil, common marmosets did not differ in day range, home range, activity budget, social organization, reproductive output, or offspring survivorship. Common marmosets exploiting a Caatinga habitat were characterized by an increase in surface area to body mass, which appears to represent an adaptation to efficiently dissipate body heat and conserve water in this very hot and dry environment